Analysis on Partial Discharge Activity in XLPE Cable by using MATLAB Software - Mat Isa, Amal Hayati; Mohd Jamail, Nor Akmal; Othman, Nordiana Azlin; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2021)
Insulation cable plays an important role in high voltage systems for transferring power or electrical signal. Quality of insulation cable should always be monitored and analyzed in order to ensure the electricity can be supplied and also to avoid operating in unhealthy conditions especially due to partial discharge that can lead to breakdown of insulators. According to the standard international of partial discharge test which is IEC 60270, the partial discharge measurement is applicable to measure of partial discharge which occurs in electrical apparatus, systems, and components when tested with DC voltage or AC voltage up to 400 Hz.  Besides, partial discharge pulse (PD pulse) is included in the basic test of equipment that is required for measuring the partial discharge according to IEC 60270. The main objective of this project is to develop and simulate partial discharge measurement with the presence of a small void inside the XLPE cable by using MATLAB software. The characteristics of partial discharge are investigated and analyzed in presence of small void with a different dimension of the cylindrical void. The three capacitances void model is used as a test object and the value of capacitances is calculated by using the formula. A circuit diagram of partial discharge measurement is built in MATLAB software with 20 kV applied voltage and a test object with dimension of voids are 2 mm × 1 mm, 2.5 mm × 1.5 mm and 3 mm × 2 mm. The result obtained show the signal of partial discharge increases as the dimension of the void increases. It can be concluded that the partial discharge becomes more serious with presence of voids, which is unfavorable to the XLPE insulation cable.